Using rule-based technique in developing the tool for finding suitable software methodology - Hanafiah, M.; Kasirun, Z.M. (2007)
Software development methodology involves many activities and processes that are carried out when building a software system. There are a lot of available methodologies; one should be suitable for a software project. However, deciding which methodology to be applied requires some assessments on the project nature and characteristics at the early project cycle. This research focuses on finding the relationship between software project factors and methodologies, and further developing a tool that can help software practitioners in choosing the most suitable methodology. Before the tool is developed, a review on several lifecycle models has been carried out in order to examine the relevant software factors. Factors like project size, complexity, requirement stability, duration, performance requirement, modularization, project team, and criticality have the main impact on some methodologies. The relationship between methodologies and software factors is formulated using rule-based approach, and managed properly by a sequence of steps; identifying the initial selection of input variables, counterexamples of bad sub rules, pruning the variables, merging categories, and identifying hypothetical examples. RETE algorithm has been chosen as the problem solving technique in managing the rules. The tool is able to help software practitioners in early decision making process to use appropriate methodology in their software project.